Cloud computing and digital media fundamentals, techniques, and applications - Li, Kuan-Ching; Li, Qing; Shih, Timothy K. (CRC Press, Taylor & Francis Group, 2014)
While some related books cover separate aspects of digital media and cloud computing, none integrate both of these areas together. Bridging the gap between digital media and cloud computing, this book brings together technologies for media/data communication, elastic media/data storage, security, authentication, cross-network media/data fusion, inter-device media interaction/reaction, data centers, platform as a service (PaaS), and software as a service (SaaS). The book also covers interesting applications involving digital media in the cloud.